Fat bodies, intimate relationships and the self in finnish and American weight-loss TV shows. Issue 2 (4th May 2023) - Ritter, Susanne
ABSTRACT: As sites where the construction of identity and selfhood take place, relationship-focused weight-loss TV shows reproduce the notion of a correlation between a woman's body size, her 'success' in romantic relationships, and the appropriate self. I analyze the weight-loss shows Revenge Body with Khloé Kardashian from the US, and Rakas, Sinusta on Tullut Pullukka (Honey, You've Become Chubby ) from Finland, investigating how relationship and body size norms, gender, and the self intertwine. I examine the shows in light of Foucault's theory of normalization. Here, normalization not only refers to the normalization of the body but also of the relationship(s) required to achieve a valid self. I suggest that the shows express a parallel between being single and on the verge of society and being fat and being on the verge of society; through solving one of the deviations (in this case, becoming thin) the other deviation (being single) can be changed and thus a "normal" life can be achieved. People learn how to normalize their bodies and their relationships, which in the end paves the way for the idea that a good body/dieting is the precondition for a relationship and an acceptable self. The shows thus reinforce that a thin body is the basis for an appropriate self and fulfilling life.